(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotatsiya. Lipoic acid, entering the tissues, binds covalently to the NH2 group of lysine of the active site of the apoenzymes of "lipoic" enzymes. These include multi-enzyme complexes that carry out keto acid reactions.